ACTIVITY ARRANGEMENT OF THE AUTONOMOUS PUBLIC SERVICE IN FOREIGN COUNTRIES - Anar Zharylkasynkyzу Сагидан; Мeruert Еrbosynovna Жумабаева (Scientific and legal journal «Bulletin of the Institute of Legislation and Legal Information of the Republic of Kazakhstan», 2022)
This article is devoted to the activity arrangement of the autonomous public service in foreign countries. In article was described the best practices of the leading countries in the department of public administration from politics and was identified the most progressive approaches in this area.